2014
DOI: 10.1016/j.molcel.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Autodeubiquitination Protects the Tumor Suppressor BAP1 from Cytoplasmic Sequestration Mediated by the Atypical Ubiquitin Ligase UBE2O

Abstract: The tumor suppressor BAP1 interacts with chromatin-associated proteins and regulates cell proliferation, but its mechanism of action and regulation remain poorly defined. We show that the ubiquitin-conjugating enzyme UBE2O multi-monoubiquitinates the nuclear localization signal of BAP1, thereby inducing its cytoplasmic sequestration. This activity is counteracted by BAP1 autodeubiquitination through intramolecular interactions. Significantly, we identified cancer-derived BAP1 mutations that abrogate autodeubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
197
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(210 citation statements)
references
References 39 publications
11
197
1
Order By: Relevance
“…It will be interesting to investigate the potential impact of this BAP1 modification on the increase of Ino80 after HU treatment. In keeping with our finding of BAP1 activity in the regulation of Ino80, it has recently been reported that the ubiquitin-conjugating enzyme UBE2O sequesters BAP1 in the cytoplasm by ubiquitinating its nuclear localization signal, resulting in an increase in Ino80 ubiquitination and a decrease in the Ino80 level 50 .…”
Section: Discussionsupporting
confidence: 92%
“…It will be interesting to investigate the potential impact of this BAP1 modification on the increase of Ino80 after HU treatment. In keeping with our finding of BAP1 activity in the regulation of Ino80, it has recently been reported that the ubiquitin-conjugating enzyme UBE2O sequesters BAP1 in the cytoplasm by ubiquitinating its nuclear localization signal, resulting in an increase in Ino80 ubiquitination and a decrease in the Ino80 level 50 .…”
Section: Discussionsupporting
confidence: 92%
“…BAP1 could be modified by post-translational modifications inhibiting its autodeubiquitination activity that lead to a cytoplasmic sequestration of BAP1 mediated by regulatory proteins, without any export signal in BAP1 gene. As a matter of fact, several ubiquitination sites of BAP1 were identified in vitro study by Mashtalir and coworkers [38].…”
Section: Case D-ii-3) Somatic Mutations In Exonmentioning
confidence: 98%
“…occur in about 5% of all tumors (COSMIC; http://cancer.sanger.ac.uk/cosmic) and in 6% considering sporadic MM, only [38]. This novel BAP1 alteration leads to a probably impaired deubiquitinase activity of BAP1 protein, suggesting its pathogenic role.…”
Section: Case D-ii-3) Somatic Mutations In Exonmentioning
confidence: 99%
“…BAP1 is also recruited to sites of DNA double strand breaks to promote repair by homologous recombination (24,28), and it is implicated in DNA replication-associated processes (29,30). Moreover, BAP1 functions appear to be regulated by posttranslational modifications, including phosphorylation and ubiquitination (24,30,31). Nonetheless, the mechanism by which BAP1 function is coordinated by its partners remains poorly defined.…”
mentioning
confidence: 99%